EVALUASI PENERAPAN GOOD CORPORATE GOVERNANCE PADA PT. BNI TBK KANTOR CABANG PEMBANTU UNSRAT - Frans, Jennifer Juliana; Karamoy, Herman; Tirayoh, Victorina Z. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
Implementation of Good Corporate Governance in the banking industry requires its own attention because the character of the banking industry is different from the industry in general. Good Corporate Governance is a bank governance that applies the principles of Transparency, Accountability, Responsibility, Independency, Fairness. The purpose of this study is to evaluate the application of the principles of Good Corporate Governance at PT. BNI Tbk kcp unsrat. The object of this research is PT BNI Tbk Kcp Unsrat. This research uses descriptive research design. The type of data used is qualitative data. Sources of data used are primary and secondary data. The research results show that with the implementation of the principles of Good Corporate Governance Bank BNI has applied the principle of openness well. The clarity of responsibility for the execution of functions and tasks is appropriate. Corporate responsibility is carried out in the presence of corporate social responsibility or CSR in the form of charitable activities. The Bank is managed independently in accordance with what has been implemented by BNI. Bank BNI Tbk has provided fair and equitable treatment.Keywords : Transparancy, Accountability, Responsibility, Independence, Fairness